Improving patient satisfaction at paediatric outpatient clinic services, Hospital Tuanku Fauziah - Hashim, Haslizawati (HRMARS, 2021)
This article aims to give an overview of the importance of customer satisfaction. In the context of the healthcare setting, patient satisfaction remains a useful indicator to measure customer satisfaction. Hence, reflecting the quality of healthcare services. Customer expectation and experience play an important role in determining customer satisfaction. Customer satisfaction is the degree to which the products or services provided by the organisation meet the expectation and how is their experience with the products or services. This article emphasised the relationship between customer expectations and experience with customer satisfaction at outpatient clinic services based on previous literature. The reliability and validity of the research instruments used to measure customer satisfaction in this study are discussed to ensure that the research instrument has high reliability and validity. Thus, proving that measuring patient expectation and the patient experience level is important in determining customer satisfaction at outpatient clinic services. The findings of this study revealed that all variables of this study are of high reliability and validity.